PENGEMBANGAN KOMPETENSI PROFESIONAL GURU DARI PERSPEKTIF MANAJEMEN KELAS - Fera Apriliyanti; Bujang Rahman; Sowiyah Sowiyah (9 772338317006)
This study aimed to identify and analyzed teachers understanding the professional competence development from a class management perspective: planning, implementation, and evaluation of the class management in Public Elementary School 2 Pesawahan, Teluk Betung Selatan. This type of research was qualitative in nature. Data were collected using observation, interviews and documentation. The collected data were then compiled, given meaning, analyzed and described. Results of this study data are: 1) planning was limited to implementing capacity mastery of learning materials to guide students in a variety of learning activities, 2) implementation was carried out through official meetings, training, workshops and the use and development of instructional media and props, 3) evaluation was relevant, systematic, objective and accountable, 4) principles of the class management were preventive and corrective actions, 5) implementation would affect the ability of students in academic resulting in proud achievement, more qualified and professional teachers in learning, and improvement in the quality of education.Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis pemahaman guru tentang perkembangan profesional kompetensi dari perspektif manajemen kelas: perencanaan, pelaksanaan, dan evaluasi pengelolaan kelas di Sekolah Dasar Umum 2 Pesawahan, Teluk Betung Selatan. Jenis penelitian ini adalah kualitatif di alam. Data dikumpulkan dengan menggunakan observasi, wawancara dan dokumentasi. Data yang terkumpul kemudian disusun, artinya diberikan, dianalisis dan dijelaskan. Hasil data penelitian ini adalah: 1) perencanaan terbatas melaksanakan kapasitas penguasaan materi pembelajaran untuk membimbing siswa dalam berbagai kegiatan belajar, 2) pelaksanaan dilakukan melalui pertemuan resmi, pelatihan, lokakarya dan penggunaan dan pengembangan instruksional media dan alat peraga, 3) evaluasi sangat relevan, sistematis, obyektif dan akuntabel, 4) prinsip-prinsip pengelolaan kelas yang tindakan preventif dan korektif, 5) implementasi akan mempengaruhi kemampuan siswa di bidang akademik sehingga guru prestasi yang membanggakan, lebih berkualitas dan profesional dalam pembelajaran, dan peningkatan kualitas pendidikan.Kata kunci: kompetensi profesional, manajemen kelas, pengembangan